Perilaku Penggunaan Kondom Pada Pelanggan WPS di Semampir Kediri - Shinta Kristianti; Zahroh Shaluhiyah; Priyadi Nugraha (Jurnal Promosi Kesehatan Indonesia, 2012)
ABSTRAKPenularan HIV-AIDS di Indonesia berkembang cepat, salah satu pemicunya adalah karena perilaku seksual yang berisiko, termasuk perilaku seksual pada pelanggan WPS. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi perilaku penggunaan kondom pada pelanggan WPS di Semampir Kediri. Penelitian ini menggunakan metode kuantitatif dengan rancangan explanatory research dengan pendekatan cross sectional. Data kualitatif dilakukan sebagai triangulasi digunakan untuk mendukung hasil analisis kuantitatif yang digali dari WPS dan mucikari sebagai cross check jawaban pelanggan WPS, cara yang digunakan adalah dengan wawancara mendalam dan FGD (Focus Group Discussion) pada WPS dan mucikari. Besar sampel adalah 66 orang. Analisa data secara univariat, bivariat dengan chi-square dan multivariat dengan regresi logistik. Hasil menunjukkan sebagian besar responden (71,2%) berperilaku konsisten dalam menggunakan kondom.Kata kunci: wanita pekerja seks (WPS), pelanggan WPS, kondom, konsistenABSTRACTCondoms Use Behavior Among Female Sex Worker’s Clients In Semampir Of Kediri;Transmission of HIV-AIDS in Indonesia is growing fast, one of the triggers are due to risky sexual behavior, including sexual behavior in FSW’s clients. This study aimed to analyze the factors that influence the behavior of condom use on the FSW’s clients in Semampir Kediri. This study used quantitative methods to the design of explanatory research with cross sectional approach. A triangulation of qualitative data used to support the results of quantitative analysis were excavated from WPS and pimps as a cross check answers FSW’s clients, the means used was to in-depth interviews and FGDs (Focus Group Discussion) on the FSW and pimps. Sample size was 66 people. Univariate data analysis, with chi-square bivariate and multivariate logistic regression. Results showed most respondents (71.2%) behave consistent in using condoms.Variables related to condom use behavior in FSW were knowledge, perception of vulnerability, severity perceived, benefits perceived, barriers perceived and perceived ability to self (self-efficacy), the availability of condoms, condom regulation, support of friends and support of FSW. Support of friend was the most influential variable on the practice of using condoms to FSW’s clients and the OR value was 19.218.Key words: female sex workers (FSW), FSW’s clients, condom, consistent